Complex care for kids Ontario: protocol for a mixed-methods randomised controlled trial of a population-level care coordination initiative for children with medical complexity. Issue 8 (1st August 2019) - Orkin, Julia; Chan, Carol Y; Fayed, Nora; Lin, Jia Lu Lilian; Major, Nathalie; Lim, Audrey; Peebles, Erin R; Moretti, Myla E; Soscia, Joanna; Sultan, Roxana; Willan, Andrew R; Offringa, Martin; et al.
Abstract : Introduction: Technological and medical advances have led to a growing population of children with medical complexity (CMC) defined by substantial medical needs, healthcare utilisation and morbidity. These children are at a high risk of missed, fragmented and/or inappropriate care, and families bear extraordinary financial burden and stress. While small in number (<1% of children), this group uses ~1/3 of all child healthcare resources, and need coordinated care to optimise their health. Complex care for kids Ontario (CCKO) brings researchers, families and healthcare providers together to develop, implement and evaluate a population-level roll-out of care for CMC in Ontario, Canada through a randomised controlled trial (RCT) design. The intervention includes dedicated key workers and the utilisation of coordinated shared care plans. Methods and analysis: Our primary objective is to evaluate the CCKO intervention using a randomised waitlist control design. The waitlist approach involves rolling out an intervention over time, whereby all participants are randomised into two groups (A and B) to receive the intervention at different time points determined at random. Baseline measurements are collected at month 0, and groups A and B are compared at months 6 and 12. The primary outcome is the family-prioritized Family Experiences with Coordination of Care (FECC) survey at 12 months. The FECC will be compared between groups using an analysis of covariance with the corresponding baseline score as the covariate. Secondary outcomes include reports of child and parent health outcomes, health system utilisation and process outcomes. Ethics and dissemination: Research ethics approval has been obtained for this multicentre RCT. This trial will assess the effect of a large population-level complex care intervention to determine whether dedicated key workers and coordinated care plans have an impact on improving service delivery and quality of life for CMC and their families. Trial registration number: NCT02928757 .